EFFECTS OF INVENTORY MANAGEMENT ON BUSINESS PERFORMANCE OF ELECTRONIC COMPANIES IN MOGADISHU, SOMALIA. - MOHAMUD, HUSSEIN ABUKAR; OMAR, DR NAGIB (IJRDO - Journal of Business Management, 2016)
The study will be examining the role of inventory management and costreduction in organization in Electronic Companies. Nowadays, we usually think ofstocks being held by organizations to allow efficient and continuous operations.Managers are aware of the vital roles inventory plays in the activities of organizations.The research design of this study will be quantitative design. In addition, clear definitionof the details of the quantitative makes the desired statistical analyses possible, andusually improves the usefulness of the results. The Electronic Companies are TargetPopulation .Research instruments can be helpful tools to your research study,. Becausethe information needed can be easily and quickly gathered from the respondents, and itcan target respondents in widely dispersed locations, in questionnaire development,Research instrument used in the Data collection is questionnaire to measure thevariable(s), characteristic(s), or information of interest, often a behavioral orpsychological characteristic. Data processing is essential for a scientific study and forensuring that we have all relevant data for making contemplated comparisons andanalysis. the study recommends that the electronic companies should not only undertakeInventory planning in order to improve operation and sustain failing businesses but alsoimprove their competitiveness and financial performance